Preventive transhepatic tract embolisation after percutaneous biliary interventions: a systematic review - Schmitz, Daniel; Chang, De-Hua; Rudi, Jochen; Hetjens, Svetlana; Ebert, Matthias (Canadian journal of gastroenterology & hepatology, 2020)
Preventive transhepatic tract embolisation (PTTE) after percutaneous biliary intervention (PBI) may reduce adverse events. The aim of this systematic review was to analyse feasibility, safety, and efficacy of PTTE with different embolic agents. A systematic literature research was performed according to the PRISMA guidelines. The identified studies were analysed concerning study quality, number of cases, indication, embolic agent, embolisation technique, success, and embolisation-related adverse events. Out of 62 identified records, 7 studies of mainly moderate study quality published through 2019 were included for further analysis. Cyanoacrylate (n = 4), gelatin sponge (n = 2), and coils (n = 1) were used as embolic agents in a total number of 314 patients. Technical success was 96-100%. Embolisation-related adverse events (glue migration, pain) occurred in 10/314 (3.2%) patients. Reduction of PBI-related pain was approved by one controlled study; haemorrhage events were reduced but not clearly significant. Overall, biliary leak, transhepatic bleeding, and PBI-related pain occurred in 7/201 (3.5%), 1/293 (0.3%), and 17/46 (36.9%) documented patients after PTTE. Adverse events which likely could not have been prevented by PTTE occurred in 23/180 (12.8%) patients. Embolic agents were not compared. In conclusion, PTTE is feasible and safe. It is effective concerning the prevention of PBI-related pain, and it may be effective concerning haemorrhage. Prevention of biliary leak is not proven. It remains unclear which embolic agent should be preferred. A prospective randomised trial including all preventable adverse events is lacking.